For what real value of is the above equation true?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rearranging terms, we get: x 3 + ( x + 1 ) 3 = ( x + 3 ) 3 − ( x + 2 ) 3 ⇒ ( 2 x + 1 ) ( x 2 + x + 1 ) = ( 3 x 2 + 1 5 x + 1 9 ) ⇒ x 3 − 6 x − 9 = 0 ⇒ ( x − 3 ) ( x 2 + 3 x + 3 ) = 0 Hence only real x= 3